Effect of TiO2 Nanofiller on Electrical Conductivity of ABS/TiO2 Polymer Nanocomposites: A Free Volume Study. (2018) - Ningaraju, S.; Munirathnamma, L.M.; Aneeshkumar, K.V.; Doreswamy, B.H.; Ravikumar, H.B.
Abstract: Acrylonitrile Butadiene Styrene (ABS) / Titanium dioxide (TiO2 ) Polymer nanocomposites with different TiO2 wt % were prepared by solution casting method. Microstructural characterization of ABS/TiO2 polymer nanocomposites was performed by Positron Lifetime Spectroscopy. The increased positron lifetime parameters viz., o-Ps lifetime (τ3 ) and free volume size (Vf ) from 0.2 to 1.0 wt% of TiO2 loading suggests the formation of interfaces due to the increased agglomeration of TiO2 nanoparticles. The increase of two orders of magnitude change in electrical conductivity (σ) of ABS/TiO2 polymer nanocomposites with the increasing free volume hole size (Vf ) as a function of TiO2 nanoparticles loading . The increased electrical conductivity (σ) with the increased free volume hole sizes (Vf ) indicates the increased interfacial space for the movements of charge carriers and TiO2 ions. Miyamoto and Shibayma model for ion conduction has been used to explore the effect of free volume hole size (Vf ) on the electrical conductivity (σ) in ABS/TiO2 polymer nanocomposites. Fourier Transform Infrared Spectroscopy (FTIR) suggests the improved chemical and physical interaction between the functional groups of TiO2 and ABS polymer side chain